2016
DOI: 10.20944/preprints201610.0048.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health Hazards Associated with Consumption of Roof-Collected Rainwater in Urban Areas in Emergency Situations

Abstract: Abstract:The greater Wellington region, New Zealand, is highly vulnerable to large earthquakes because it is cut by active faults. Bulk water supply pipelines cross the Wellington Fault at several different locations, and there is considerable concern about severe disruption of the provision of reticulated water supplies to households and businesses in the aftermath of a large earthquake. A number of policy initiatives have been launched encouraging householders to install rainwater tanks to increase post-disa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Várias metodologias e modelos foram desenvolvidos para quantificar o potencial de captação do telhado (ALADENOLA; ADEBOYE, 2010; ISHAKU; MAJID; JOHAR, 2012), os critérios de seleção, a relação custo/benefício (KHASTAGIR; JAYASURIYA, 2011), o dimensionamento de reservatórios (GHISI, DOI: 10.1590Oliveira, J.N. ;Libânio, M. 2010; GHISI; SCHONDERMARK, 2013), os impactos na saúde dos consumidores (HEYWORTH et al, 2006;MARCYNUK et al, 2009;STEWART et al, 2016) e o desempenho em geral (SINGH et al, 2013).…”
Section: Introdução E Relevânciaunclassified
“…Várias metodologias e modelos foram desenvolvidos para quantificar o potencial de captação do telhado (ALADENOLA; ADEBOYE, 2010; ISHAKU; MAJID; JOHAR, 2012), os critérios de seleção, a relação custo/benefício (KHASTAGIR; JAYASURIYA, 2011), o dimensionamento de reservatórios (GHISI, DOI: 10.1590Oliveira, J.N. ;Libânio, M. 2010; GHISI; SCHONDERMARK, 2013), os impactos na saúde dos consumidores (HEYWORTH et al, 2006;MARCYNUK et al, 2009;STEWART et al, 2016) e o desempenho em geral (SINGH et al, 2013).…”
Section: Introdução E Relevânciaunclassified
“…Despite all the advantages of using rainwater, it must be analyzed before use, because there may be the presence of microbiological and chemical contaminants (Stewart et al, 2016), which could cause a potential health hazard for the consumer (Angala et al, 2019). Therefore, assessing the quality of urban rainwater remains a complex and challenging field, given the large number of factors involved (Behmel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic lead use has had severe negative effects on wildlife globally (Tranel & Kimmel, 2009;Vallverdú-Coll et al, 2015). However, despite the high levels of heavy metals present in cities (Stewart et al, 2016), the impacts of lead on wildlife inhabiting urban habitats are rarely studied (Sriram et al, 2018). Research exploring lead poisoning in Wellington's kākā population has reported that a large proportion of the population (43%) have elevated leadblood concentrations, likely from ingesting roofing materials.…”
Section: Introductionmentioning
confidence: 99%